2012
DOI: 10.1111/j.1944-9720.2012.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Study Abroad Students in Intercultural Learning Through Blogging and Ethnographic Interviews

Abstract: The study involved 16 American undergraduate students who used weekly blogs and conducted ethnographic interviews with native speakers to develop their intercultural competence over the course of one semester abroad. Selected blog entries, post‐surveys, and final interviews were collected and analyzed to report the findings. The results show that blog tasks afforded additional opportunities for students to refl ect upon cross‐cultural issues and exchange cultural perspectives with native informants. Blog entri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 32 publications
1
67
0
1
Order By: Relevance
“…This can take place prior to the departure, during the term abroad, and after the re-entry (Marx & Moss, 2011;Pedersen, 2010). The form of reflection could be a cultural learning journal or a blog documenting their stays abroad (Kruse & Brubaker, 2007;Lee, 2012;Stebleton, Soria, & Cherney, 2013). Moreover, supportive faculty and staff can be of importance to help international students with cross-cultural transition by reducing their pressure and easing their anxiety.…”
Section: International Journal Of Research Studies In Education 63mentioning
confidence: 99%
See 1 more Smart Citation
“…This can take place prior to the departure, during the term abroad, and after the re-entry (Marx & Moss, 2011;Pedersen, 2010). The form of reflection could be a cultural learning journal or a blog documenting their stays abroad (Kruse & Brubaker, 2007;Lee, 2012;Stebleton, Soria, & Cherney, 2013). Moreover, supportive faculty and staff can be of importance to help international students with cross-cultural transition by reducing their pressure and easing their anxiety.…”
Section: International Journal Of Research Studies In Education 63mentioning
confidence: 99%
“…Instructors could modify their teaching styles and course assessments to accommodate students' language levels (Andrade, 2006). Finally, close interaction with native speakers and ethnographic interviews with native informants can be beneficial for gaining students' both intercultural knowledge and language skills in the study abroad context (Adams, 2006;Kruse & Brubaker, 2007;Lee, 2012;Martinsen, 2011). Hence, instructors and institutions need to create more opportunities for students to meaningfully interact with native speakers in and outside of classroom.…”
Section: International Journal Of Research Studies In Education 63mentioning
confidence: 99%
“…Technologies have made it possible to create environments for people to communicate with people from diverse cultures with relative ease. There is a good deal of research which shows that computer-mediated communication (CMC) and telecollaborative projects provide environments for students to communicate with people from diverse cultures and help students to develop intercultural competence [21], [16], [17] and [18] Examples of blogging, podcasting, email exchanges, and chat rooms used for cultural exchanges have appeared in the literature, and have shown to be motivating for the participants [8], [17] It has also been suggested that adopting technology to learn about cultures can help learners to reflect on both their own culture and the target culture, contributing to making them more interculturally competent [4], [11], as well as facilitating development from ethnocentrism to ethnorelativism [16], [21] point out that there is still a lack of research in technology-oriented intercultural learning environments, with a need for more empirical studies that evaluate different approaches to developing intercultural competence are needed, as well as pedagogies that balance cognitive, affective, and behavioural perspectives.…”
Section: Technology and Developing Intercultural Competencementioning
confidence: 99%
“…There are various teaching method and materials that can be used to maximize students' cultural learning as proposed by several researchers, such as the research conducted by Robinson-Stuart and Nocon (1996), Liaw and Johnson (2001), Bateman (2004), Lee (2012), Dewi (2012), Chao (2013), Rodriguez (2014), Truong and Tran (2014), and Maryani (2016). Only the research by Dewi (2012) and Maryani (2016) are conducted in Indonesia, whereas the rest are conducted abroad.…”
Section: Introductionmentioning
confidence: 99%
“…The results show teachers' enhanced attitudes towards Spanish speakers and Hispanic cultures, greater competencies in communicating across cultures and awareness of culture's influence. The third is Lee (2012) that researched 16 American undergraduate Spanish students. The instruments used are personal blogs using ethnographic interviews, a questionnaire, and a survey.…”
Section: Introductionmentioning
confidence: 99%